2017
DOI: 10.3748/wjg.v23.i14.2453
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive molecular analysis ofHelicobacter pylori: Is it time for tailored first-line therapy?

Abstract: The main problem of Helicobacter pylori (H. pylori) infection management is linked to antibiotic resistances. This phenomenon has grown in the last decade, inducing a dramatic decline in conventional regimen effectiveness. The causes of resistance are point mutations in bacterial DNA, which interfere with antibiotic mechanism of action, especially clarithromycin and levofloxacin. Therefore, international guidelines have recently discouraged their use in areas with a relevant resistance percentage, suggesting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 42 publications
1
40
0
4
Order By: Relevance
“…Previous studies using the PCR-Restriction Fragment Length Polymorphism (RFLP) system have shown the high frequency of the A2143G or A2144G mutations in clarithromycin-resistant H. pylori in both the United States and Europe [16,26]. There was no mutation at position 2144 in our study, indicating that the main 23S rRNA gene mutations inducing clarithromycin resistance are dissimilar in western and eastern countries [14]. Moreover, we documented that clinically insignificant point mutations had little influence on the H. pylori eradication rate; however, this has yet to be confirmed and fully elucidated.…”
Section: Discussionsupporting
confidence: 42%
See 3 more Smart Citations
“…Previous studies using the PCR-Restriction Fragment Length Polymorphism (RFLP) system have shown the high frequency of the A2143G or A2144G mutations in clarithromycin-resistant H. pylori in both the United States and Europe [16,26]. There was no mutation at position 2144 in our study, indicating that the main 23S rRNA gene mutations inducing clarithromycin resistance are dissimilar in western and eastern countries [14]. Moreover, we documented that clinically insignificant point mutations had little influence on the H. pylori eradication rate; however, this has yet to be confirmed and fully elucidated.…”
Section: Discussionsupporting
confidence: 42%
“…This study has some limitations. First, we could not perform H. pylori culture and antibiotic susceptibility testing [14]. It is reported that there may be discordance between genotype and phenotype [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…International guideline agencies have recently rejected the use of clarithromycin in areas with a resistance rate higher than 15%. Nevertheless, guidelines are designed for the clinical practice within an empirical setting, that is, where susceptibility testing is unavailable, epidemiological data are taken in account to allow for the rational use of antibiotics [31]. Before 2007, between the years 1999 and 2006, in the central-western region of Colombia, the resistance to metronidazole, clarithromycin, and amoxicillin was found in 82, 3.8, and 1.9% of 106 H. pylori isolates respectively.…”
Section: Introductionmentioning
confidence: 99%